2006
DOI: 10.4049/jimmunol.176.5.2969
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase-Activating Polypeptide 27 Is a Functional Ligand for Formyl Peptide Receptor-Like 1

Abstract: Although the neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) has been implicated in the regulation of several immune responses, its target receptors and signaling mechanisms have yet to be fully elucidated in immune cells. In this study, we found that PACAP27, but not PACAP38, specifically stimulated intracellular calcium mobilization and ERK phosphorylation in human neutrophils. Moreover, formyl peptide receptor-like 1 (FPRL1) was identified as a PACAP27 receptor, and PACAP27 was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…The PACAP-27/FPR1 activation is responsible for the associated induced ROS production, as well as chemotactic migration CD11b surface upregulation, and cytokine production. 27 In our study, we found that either PACAP-38 or VIP inhibited fMLF-induced ROS response in whole blood in favor of a predominant VPAC1 interaction in line with VIP/VPAC1 major control of immunological answer in animal studies. 28 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The PACAP-27/FPR1 activation is responsible for the associated induced ROS production, as well as chemotactic migration CD11b surface upregulation, and cytokine production. 27 In our study, we found that either PACAP-38 or VIP inhibited fMLF-induced ROS response in whole blood in favor of a predominant VPAC1 interaction in line with VIP/VPAC1 major control of immunological answer in animal studies. 28 .…”
Section: Discussionsupporting
confidence: 60%
“…However, PACAP-27, unlike the predominant extended peptide PACAP-38, stimulates cytoplasmic calcium mobilization and phosphorylation ERK in both human monocytes and neutrophils and promote ROS production by itself. 26,27 The proposed explanation is that PACAP-27 is a functional ligand of the high-affinity receptor FPR1 of fMLF present in phagocytes. The PACAP-27/FPR1 activation is responsible for the associated induced ROS production, as well as chemotactic migration CD11b surface upregulation, and cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that in neutrophils, the proinflammatory effects of PACAP were mediated by VPAC1 and FPRL1, the low-affinity FPR receptor [43]; in this study, VIP was reported to have no effect on calcium or ERK phosphorylation. In contrast, we found that in monocytes, VIP increases cAMP, phosphorylates Akt, ERK, and p38, and up-regulates CD11b, CD35 membrane expression, and MMP-9 secretion, indicating that monocytes are sensitive to VIP.…”
Section: Discussionmentioning
confidence: 44%
“…During recent years, the role of PACAP in immunoregulation has been partially elucidated in mammals [11][12][13][14] demonstrating that PACAP modulates both innate and adaptive immunity. In general, only preliminary studies on PRP functions have been done in mammals [15,16], therefore studies on PRP functions over immunity are still missing.…”
Section: Introductionmentioning
confidence: 99%